Beyond Deep Incarnation: Rethinking Christology in Radical Lutheran Terms. (September 2014) - Peterson, Daniel J.
Abstract This article takes the demise of Christendom and what Diana Butler Bass calls the end of religion as its point of departure for a "radical" rethinking of God in fully kenotic terms. It rejects any vestige of otherworldly transcendence as a temptation to escapism, inviting us instead to seek God's complete presence among us here in the world. Going beyond Niels Gregersen's understanding of the deep incarnation of the Logos and starting instead with a complete commitment to the infra‐Lutheranum, the author presents a radical Lutheran theology that embraces a total kenosis of God whose liberating and life‐giving reappearance we must find implicit among us in unexpected places, not least of which might include the embers of a dying church or the crumbling of our religious institutions.